Analysis of knowledge, attitude, and practices (KAP) regarding food allergies in social network users in Costa Rica - López Calvo, Rebeca (2022)
Limited information exists about food allergies in Costa Rica. The objective of this research was to apply a knowledge, attitudes, and practices (KAPs) study to establish an initial database for the country. Data were collected through an online questionnaire published in 2020 and cluster analysis was used to create groups based on responses to questions about specific areas. General scores were obtained for each category and clusters were compared. A total of 1058 answers were considered valid, and 48% of participants reported that they suffered food allergies, but only about half of those indicated that they had a medical diagnosis. Most participants (83.1%) were grouped in categories with a medium to high level of knowledge. Incomplete knowledge about cross-contact was observed and there was confusion regarding the concepts of allergy and intolerance. Three attitude groups were formed and 92% of all participants had high scores. Three groups were also formed based on responses to questions about practices. Better practices were identified in a group that contained 62% of the participants and included persons who habitually read lists of ingredients on product labels and menus or/and ask restaurant staff about ingredients. There was a positive correlation between knowledge and practices; the same was found between knowledge and attitudes, and attitudes and practices. Results of this study are in agreement with the KAP model: knowledge is necessary in order to achieve significant changes in practices. This study confirms the importance of proper clinical diagnoses and the application of prevalence studies.